Evaporation of sessile ethanol-water droplets on a critically inclined heated surface. (October 2020) - Katre, Pallavi; Gurrala, Pradeep; Balusamy, Saravanan; Banerjee, Sayak; Sahu, Kirti Chandra
Highlights: Evaporation of binary sessile ethanol-water droplets on an inclined substrate is investigated. Thermo-solutal Marangoni convection is studied as function of the substrate temperature. Droplet exhibits two distinct oscillatory water-rich cold regions at early stage of evaporation. Thermal pulsations along the incline are created as ethanol-rich cells collapse. Evaporation rate exhibits a universal behaviour at different substrate temperatures. Graphical abstract: Abstract: The evaporation of a binary sessile ethanol-water droplet on an inclined substrate is studied experimentally just below the critical sliding angles for different substrate temperatures. A customized goniometer equipped with a CMOS camera and an infrared (IR) camera is used. The droplet is observed to remain pinned in the advancing side during the evaporation process, while the receding side contracts. The asymmetry in the advancing and receding contact angles of the droplet on inclined substrate results in complex thermo-solutal Marangoni convection that is captured through IR images. The droplet exhibits two distinct oscillatory water-rich cold regions around the advancing contact line during the early stage of evaporation, while the more volatile and lighter ethanol creates a hotter and rapidly evaporating cell near the receding side. As ethanol evaporates away, the ethanol rich cells collapse producing thermal pulsations along the incline. Subsequently, the thermal patterns become similar to that of the pure-water droplet. It is also observed that the thermo-solutal driven oscillatory convection increases with increasing substrate temperature. Despite the complexity in convection dynamics, the evaporation rate exhibits a universal behavior in the normalized time at different substrate temperatures which can be represented by piecewise linear fits at the early and late stages of evaporation.